Children and families seeking asylum in Northern Norway : living conditions and mental health - Lauritzen, Camilla; Sivertsen, Hilde Buvik (International Migration, 2012)
The mental health of children seeking asylum and their families is a somewhat neglected area of research. Research on refugee children and children living with adversities suggests that environmental factors are crucial in preventing mental health problems. This study aims at identifying central environmental conditions that affect the mental health of children living with their families at governmental asylum processing centers in Northern Norway. This study has a qualitative design, and is based on 11 focus group interviews with the staff at asylum processing centers. The interviews were transcribed verbatim and analyzed focusing on important risk and protective factors for mental health problems presented by the informants. Results pointed out time spent at asylum centers and the parent’s mental health as the most important risk factors. Schooling, activities, general living conditions and poor economy were also seen as crucial. The findings suggest that these children are indeed vulnerable, and in high risk of developing mental health problems. Their rights are however open to local interpretations, and they fall between two stools; their right to proper healthcare, and national and international immigration policies.